Noncommunicable diseases associated with bleeding disorders, hospitalization, and mortality in patients with dengue in Mexico: A national analysis of confirmed cases in 2024. - Diego Rolando Hernández-Galdamez; Miguel Ángel González-Block; Daniela Karola Romo-Dueñas; Erick Antonio Osorio-López; Rosalba Cerón-Meza; Pablo Méndez-Hernández (PLoS Neglected Tropical Diseases)
Background In Mexico, some of the most prevalent noncommunicable diseases (NCDs) among adults are diabetes, hypertension, and chronic kidney disease (CKD). Mexico is currently facing a syndemic characterized by the convergence of dengue and NCDs. This study aims to describe and analyze the association between the prevalence of NCDs and hospitalization, the presence of hemorrhagic disorders, and death in all officially confirmed cases of dengue in Mexico during 2024. Methodology/principal findings This cross-sectional study was carried out through a secondary analysis of the confirmed cases of dengue reported in 2024. We assessed the associations between NCDs and the probability of hospitalization, bleeding disorders, and death, using one logistic regression model for each clinical outcome. We adjusted the three models for age, sex, social security affiliation, ethnicity and for each of the NCDs (diabetes, hypertension, chronic kidney disease, immunosuppression, cirrhosis, and peptic ulcer disease). The most common noncommunicable diseases were diabetes, hypertension, CKD, and immunosuppression. For hospitalization, CKD had the strongest association (OR 5.74), followed by immunosuppression (OR 2.84), peptic ulcer disease (OR 2.33), and diabetes (OR 2.10). We found significant associations between bleeding disorders and several NCDs (diabetes, peptic ulcer disease, immunosuppression, cirrhosis, and hypertension) compared to people without these conditions. People with CKD, peptic ulcer disease and diabetes, had more odds for death compared to those without these comorbidities. Conclusions/significance We found a significant association between several comorbidities and worse clinical outcomes in patients with dengue, such as hospitalization, bleeding disorders, or death. The syndemic of NCDs and dengue in Mexico has been rapidly increasing, and this problem needs to be addressed. This work confirms and extends the findings of previous studies and suggests that patients with these comorbidities have worse clinical outcomes.